Good nutrition program: annual survey year two. (2018)
SUMMARY: Nepal has made tremendous reductions in maternal and child undernutrition since the mid-1990s but continues to face high burdens. Among children under five years, 36% are stunted, 10% are wasted and 27% are underweight. Additionally, 17% of women of reproductive age (WRA) (15-49 years) are underweight while 41% are anemic (Nepal Demographic and Health Survey, 2016). The Government of Nepal (GoN) is currently rolling out the second phase of a national Multi-Sectoral Nutrition Plan (MSNP), with the support of external development partners (EDPs). Suaahara II (SII) is a USAIDfunded multisectoral nutrition program, aligned with Nepal's MSNP, being implemented in 42 of Nepal's 77 districts from 2016 to 2021. SII aims to reduce the prevalence of stunting, wasting and underweight among children under five years of age and to reduce the prevalence of anemia among WRA and children 6-59 months of age. SII works across thematic areas including nutrition, health and family planning (FP), water, sanitation and hygiene (WASH), agriculture/homestead food production (HFP), and governance, using a gender equality and social inclusion (GESI) approach for all interventions. Annual surveys are a key component of SII's monitoring system. The primary purpose is to monitor progress over time related to key SII inputs, outputs, outcomes and impacts in intervention areas. The first SII annual monitoring survey was conducted between June to September 2017 among a representative sample of households with a child under five years, by New ERA, a local survey firm. At the household level, mothers were the primary survey respondents. A primary male (or female, if male unavailable) household decision maker was also interviewed. Additionally, the youngest child's grandmother and an adolescent girl (10-19 years), when residing in the same household, were also interviewed. Data was also collected from Female Community Health Volunteers (FCHVs) and 1 key informant from each health facility in the sampled areas. The household surveys included questions related to exposure, knowledge and practices for each of the thematic areas. Anthropometric status was also assessed for all women of reproductive age, children under five, and adolescent girls residing in the household. FCHV and health facility surveys collected information on their exposure to training, motivation, supervision, work-related activities, knowledge, skills, and availability of supplies/services. The final survey sample included 3642 households, 192 FCHVs and 96 health facilities in 2017. Similar to the first annual survey, data collection for the second SII annual survey was conducted between July to September 2018, again, among a representative sample of households with a child under five years. The second annual survey was conducted by the same survey firm, New ERA and in the same sample clusters. Mothers were the primary survey respondents. A primary male (or female, if male unavailable) household decision maker was also interviewed. Unlike the first annual survey, grandmothers, health facility workers, and FCHVs were not respondents in the 2018 annual survey and at the household level, anthropometry and hemoglobin were not collected. There was some variation in survey modules and questions in the 2017 and 2018 tools, but key modules and questions needed for calculation of indicators along SII's primary pathways to impact remained unchanged. In 2018, the final survey sample included 3648 households. When comparing changes in key indicators between 2017 and 2018, trends in the expected directions based on the interventions can be seen across all intervention areas: nutrition, health, WASH, and agriculture and in many cases are large improvements for a one-year period. Some of the key statistically significant (P<0.05) differences include: children 6-23 months receiving foods from 4 or more groups increased from 47% to 54% (P:0.01), WRA receiving foods from 5 or more groups increased from 36% to 42% (P:<0.000), households practicing correct use of water treatment technologies increased from 14% to 19% (P<0.000), households with soap and water at a handwashing station increased from 37% to 49% (P<0.000), pregnant women weighed during most recent antenatal care (ANC) visit (among those who received ANC) increased from 87% to 93% (P:0.01), children 0-2 years weighed in the past month increased from 18% to 22% (P<0.000), newborns receiving postnatal checkup within 24 hours of birth increased from 74% to 79% (P<0.000), and households with homestead gardens meeting minimum criteria increased from 9% to 23% (P:0.02) (Table 1). Table 1 Key indicators from 2017 and 2018 surveys Indicators 2017 2018 P-value Mean (SD)/% Mean (SD)/% Maternal health and nutrition Women's Dietary Diversity (10 food groups): Mean number of food groups consumed by women of reproductive age (N=3640, 3648) 4.1 4.3 <0.000 Minimum dietary diversity among WRA (foods from 5 or more of 10 food groups) (N=3640, 3648) 35.6% 41.6% <0.000 Women consuming all 180 tablets of Iron and folic acid (IFA) during pregnancy (N=1835, 1899) 52.4% 59.1% <0.000 Pregnant women weighed during most recent ANC visit, among those who received ANC (N=1772, 1855) 86.7% 93.4% <0.000 Births receiving at least 4 ANC visits during pregnancy (N=1848, 1910) 79.5% 85.5% <0.000 Births attended by a skilled birth attendant (N=1848, 1910) 73.2% 77.2% 0.004 WRA in union who are currently using a modern method of contraception (N=3642, 3648) 34.2% 33.2% 0.40 Child health and nutrition Low birth weight (N=621, 702) 11.1% 8.3% 0.09 Newborns receiving postnatal health check within 24 hours of birth (N=1820, 1896) 73.5% 79.1% <0.000 Children 0-2 years weighed in the past month (N=1850, 1910) 17.8% 22.2% <0.000 Children born in the last 24 months who were put to the breast within one hour of birth (N=1843, 1902) 67.5% 69.3% 0.03 Exclusive breastfeeding of children under 6 months of age (N=455, 450) 70.6% 71.1% 0.86 Children 12-15 months of age who are breastfed (N=201, 265) 98.5% 99.6% 0.23 Minimum acceptable diet among children 6-23 months of age (N=1385, 1460) 37.5% 45.7% <0.000 Minimum dietary diversity among children 6-23 months of age (foods from 4 or more of 7 food groups (N=1385, 1460) 46.7% 53.5% 0.001 Infants 6-8 months of age who receive solid, semisolid or soft foods (N=214, 210) 91.6% 88.1% 0.26 Breastfed and non-breastfed children 6-23 months of age, who received solid, semi-solid, or soft foods (N=1385, 1460) 81.2% 87.8% <0.000 Children 6-23 months of age who received an ironrich food or iron-fortified food (N=1385, 1460) 84.2% 88.6% 0.001 Sick children 6-23 months of age fed more during illness (N=593, 541) 38.5% 38.8% 0.90 Children <5 years who had diarrhea in the prior two weeks (N=3642, 3648) 11.1% 9.1% 0.01 Sick children (diarrhea) given oral rehydration solution (ORS) and zinc (N=306, 247) 22.6% 21.9% 0.71 Households with a child aged 0-2 years who had contact with the FCHV in the previous month (N= 1848, 1909) 52.5% 58.5% 0.002 Water, sanitation and hygiene Households using an improved sanitation facility (N=3644, 3647) 86.6% 88.3% 0.03 Households practicing correct use of household water treatment technologies (N=3630, 3646) 14.3% 19.0% <0.000 Households with soap and water at a handwashing station commonly used by family members (N=3629, 3646) 37.1% 48.5% <0.000 Women practices handwashing at 6 critical times (N=3640, 3648) 7.8% 19.0% <0.000 Agriculture/Enhanced Homestead Food Production Households with homestead gardens meeting minimum criteria (N=796, 798) 8.7% 23.2% <0.000 Households with chickens (N=796, 798) 47.9% 51.4% 0.11 Households with a child aged 0-2 years who received HFP inputs from village model farmers (VMFs) and/or graduated HFP beneficiaries (N=414, 436) 17.4% 29.8% <0.000 Households who sold surplus vegetable production in the past year (N=796, 798) 21.7% 18.7% 0.30 Households who sold surplus eggs produced in the past month (N=381, 470) 3.9% 2.1% 0.05 Households that used revenue earned by selling HFP surplus for nutrition, in the previous years (N=186, 152) 20.4% 30.9% 0.07